Proceedings 29th Annual International Symposium on Computer Architecture
DOI: 10.1109/isca.2002.1003573
|View full text |Cite
|
Sign up to set email alerts
|

Power and performance evaluation of globally asynchronous locally synchronous processors

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 12 publications
0
54
0
Order By: Relevance
“…In order to obtain this number, Google Scholar [8] was used. Important practical reasons for this are that Google Scholar is freely available to anyone with an Internet connection, has better citation indexing and "Scheduling for reduced CPU energy," M. Weiser, B. Welch, A. J. Demers, and S. Shenker [11] "Automatic performance setting for dynamic voltage scaling," K. Flautner, S. Reinhardt, and T. Mudge [12] "The design, implementation, and evaluation of a compiler algorithm for CPU energy reduction," C. Hsu and U. Kremer [13] "Energy-conscious compilation based on voltage scaling," H. Saputra "Identifying program power phase behavior using power vectors," C. Isci and M. Martonosi [18] "Live, runtime phase monitoring and prediction on real systems with application to dynamic power management," C. Isci, G. Contreras, and M. Martonosi [19] "Power and performance evaluation of globally asynchronous locally synchronous processors," A. Iyer and D. Marculescu [20] "Toward a multiple clock/voltage island design style for power-aware processors," E. Talpes and D. Marculescu [21] "Dynamic frequency and voltage control for a multiple clock domain microarchitecture," G. Semeraro, D. H. Albonesi, S. G. Dropsho, G. Magklis, S. Dwarkadas, and M. L. Scott [22] "Formal online methods for voltage/frequency control in multiple clock domain microprocessors," Q. Wu, P. Juang, M. Martonosi, and D. W. Clark [23] "Energy-efficient processor design using multiple clock domains with dynamic voltage and frequency scaling," G. Semeraro, G. Magklis, R. Balasubramonian, D. H. Albonesi, S. Dwarkadas, and M. L. Scott [24] "Joint dynamic voltage scaling and adaptive body biasing for heterogeneous distributed real-time embedded systems," L. Yan, J. Luo, and N. K. Jha [29] Core Blocks-Pipeline-Dynamic…”
Section: List Of Selected Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to obtain this number, Google Scholar [8] was used. Important practical reasons for this are that Google Scholar is freely available to anyone with an Internet connection, has better citation indexing and "Scheduling for reduced CPU energy," M. Weiser, B. Welch, A. J. Demers, and S. Shenker [11] "Automatic performance setting for dynamic voltage scaling," K. Flautner, S. Reinhardt, and T. Mudge [12] "The design, implementation, and evaluation of a compiler algorithm for CPU energy reduction," C. Hsu and U. Kremer [13] "Energy-conscious compilation based on voltage scaling," H. Saputra "Identifying program power phase behavior using power vectors," C. Isci and M. Martonosi [18] "Live, runtime phase monitoring and prediction on real systems with application to dynamic power management," C. Isci, G. Contreras, and M. Martonosi [19] "Power and performance evaluation of globally asynchronous locally synchronous processors," A. Iyer and D. Marculescu [20] "Toward a multiple clock/voltage island design style for power-aware processors," E. Talpes and D. Marculescu [21] "Dynamic frequency and voltage control for a multiple clock domain microarchitecture," G. Semeraro, D. H. Albonesi, S. G. Dropsho, G. Magklis, S. Dwarkadas, and M. L. Scott [22] "Formal online methods for voltage/frequency control in multiple clock domain microprocessors," Q. Wu, P. Juang, M. Martonosi, and D. W. Clark [23] "Energy-efficient processor design using multiple clock domains with dynamic voltage and frequency scaling," G. Semeraro, G. Magklis, R. Balasubramonian, D. H. Albonesi, S. Dwarkadas, and M. L. Scott [24] "Joint dynamic voltage scaling and adaptive body biasing for heterogeneous distributed real-time embedded systems," L. Yan, J. Luo, and N. K. Jha [29] Core Blocks-Pipeline-Dynamic…”
Section: List Of Selected Examplesmentioning
confidence: 99%
“…In early work on this topic [20,21], they consider opportunities of DVFS application to GALS. They found that GALS designs are initially less efficient than synchronous architecture but that there are internal slacks that could be exploited.…”
Section: Dvfs For Multiple Clock Domain Processorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu [5] proposed a compiler directed dynamic frequency and voltage scaling mechanism. Iyer [6] evaluated power and performance of globally asynchronous locally synchronous processors. Milutinovic [7] worked on pipeline design tradeoffs on the basis of a 32-bit gallium arsenide processor.…”
Section: Related Workmentioning
confidence: 99%
“…In the multiple clock domain (MCD) [35] technique, the hardware is separated into modules based on certain attributes, with each domain having its own clock. The synchronization of domains and power reduction in this technique are referred to as The globally-asynchronous locally-synchronous (GALS) design is one of the popular techniques to implement MCD systems, and the available power-reduction techniques are also beneficial for this kind of implementation [36]. The supply voltage of MCD may be uniform.…”
Section: Low-power Designmentioning
confidence: 99%